2017
DOI: 10.1039/c7sc00415j
|View full text |Cite
|
Sign up to set email alerts
|

Selective single molecule nanopore sensing of proteins using DNA aptamer-functionalised gold nanoparticles

Abstract: DNA aptamer-modified gold nanoparticles that act as a molecular carrier through a nanopore sensor facilitate the selective detection of target proteins in mixed analyte populations with enhanced signal-to-noise ratio and event rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 68 publications
1
110
0
1
Order By: Relevance
“…[14] Furthermore to enable selective single-molecule sensing with high sensitivity, Keyser et al developed a DNA carrier-based antibody detection technique using DNA nanostructures which combine antigen presentation alongside a unique barcode identifier made up of dumbbell hairpin protrusions. [17] Using a different approach, Long et al showed that nanopipettes can be employed for label-and carrier-free detection of individual immune-complexes. [17] Using a different approach, Long et al showed that nanopipettes can be employed for label-and carrier-free detection of individual immune-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Furthermore to enable selective single-molecule sensing with high sensitivity, Keyser et al developed a DNA carrier-based antibody detection technique using DNA nanostructures which combine antigen presentation alongside a unique barcode identifier made up of dumbbell hairpin protrusions. [17] Using a different approach, Long et al showed that nanopipettes can be employed for label-and carrier-free detection of individual immune-complexes. [17] Using a different approach, Long et al showed that nanopipettes can be employed for label-and carrier-free detection of individual immune-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] In the last two decades, nanoporebased single-entity sensing techniques have been developed into powerful methods to study different properties of various nanoscale entities. [9][10][11][12][13][14][15][16] To further improve the sensitivity and selectivity of the ionic current detection based nanopore technique, as well as add new functionalities to it, it is of great interest to bring new sensing modules to the resistive-pulse based detection method. [9][10][11][12][13][14][15][16] To further improve the sensitivity and selectivity of the ionic current detection based nanopore technique, as well as add new functionalities to it, it is of great interest to bring new sensing modules to the resistive-pulse based detection method.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they have been applied to the detection of metabolites (Alsager et al, ), proteins (Billinge, Broom, & Platt, ; Billinge & Platt, ; Siwy et al, ), DNA sequencing (Branton et al, ; Majd et al, ; Yeh, Zhang, Qian, & Hsu, ), epigenetics (Healey, Rowe, Siati, Sivakumaran, & Platt, ; Rand et al, ) and cellular vesicles (Kamińska et al, ; Nizamudeen, Markus, Lodge, Parmenter, & Platt, ). An increasingly common strategy in RPS utilizes nanomaterials as carriers of recognition elements to selectively bind to the target (Ali, Nasir, & Ensinger, ; Billinge et al, ; Billinge & Platt, , ; Lin, Ivanov, & Edel, ; Mayne, Christie, & Platt, ; Rotem, Jayasinghe, Salichou, & Bayley, ; Sze, Ivanov, Cass, & Edel, ). The carrier acts as a support for multiple ligands enhancing the signal and facilitating multiplexed assays (Blundell, Mayne, Billinge, & Platt, ; Platt, Willmott, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Once immobilized onto a carrier, the binding of the analyte can be monitored via two mechanisms. The first is a change in size or shape of the DNA (Lin et al, 2017). The second is a change in charge density around the carrier (Alsager et al, 2014;Billinge et al, 2014), measured through a change in translocation velocity, Figure 1, providing quantitative information (Billinge et al, 2014;Billinge & Platt, 2015a;Blundell, Mayne, Lickorish, Christie, & Platt, 2016).…”
mentioning
confidence: 99%